Prevalence and pattern of endocrinological abnormalities in oligospermic and azoospermic patients. - Al Najar, Ali F. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Hormones have very important role in spermatogenesis and production capacity of testis. Disturbances in their vlevels can be very crucial in dysfunction of testis which results in men infertility. This study carried out to evaluate the hormonal disturbances in men infertility and its correlation with semen parameters and types of infertility. Patients and Methods: Blood and semen samples were collected from 91 infertile men and 20 healthy and fertile control who attended Al-Kadymiah hospital and some private clinics in Baghdad from January to December 2009.Semen and serum samples were analysed for semen parameter and FSH, LH, Testosterone and prolactin levels. Results: Fifty one (56%) of infertile men were found with azoospermia, 22(24%) were with mildoligospermia and 18(20%) were with severoligospermia.Semen analysis of infertile men showed very low quality parameters with a non homogenized hormonal results.Elevation of FSH and LH with low level of testosterone were detected in azoospermic and Severoligospermic groups, while elevation of FSH with hyperprolactinaemia were detected in mildoligospermia. Conclusion: FSH and LH elevated levels were found to have a major role in azoospermia and severoligospermia, while prolactine and FSH elevations were correlated with mildoligospermia. Also these hormonal disturbances were found to associate with the quality of the semen where the low semen quality parameters detected in those with FSH, LH elevation and low level of testosterone. We concluded that hormonal disturbances can be considered as a reliable indicator to distinguish between non obstructive (over levels of FSH, LH and decrease level of testosterone) and obstructive (over levels of FSH,prolactin) types of infertility which is very important in therapy.